Metastatic Non-Small-Cell Lung Cancer in the Setting of Unilateral Agenesis of the Left Pulmonary Artery: A Case Report and Comprehensive Literature Review - John Agzarian; Jakub Kadlec; Lori Whitehead; Yaron Shargall (Case Reports in Oncological Medicine)
Unilateral absence of the pulmonary artery (UAPA) represents a rare condition that is often associated with cardiac congenital abnormalities but can also be relatively asymptomatic and indolent. There is a lack of consensus regarding the management of UAPA. However, in the setting of associated complications and ongoing infection, pulmonary resection is advocated. Although rare, the association between UAPA and bronchogenic carcinoma has been previously reported in seven published cases. In the majority of these, anatomic lung resection (most commonly with pneumonectomy) was curative. We present the first reported case of ipsilateral metastatic non-small-cell lung cancer- (NSCLC-) associated UAPA in a 47-year-old patient with ventilator-dependent hypoxic respiratory failure and bronchorrhea, who had been lost to follow-up for 8 years. Initial investigations did not yield evidence of malignancy, and confirmation of metastatic disease was made intraoperatively at the time of thoracotomy. The findings demonstrated evidence of diffuse metastatic pleural disease with lymphangitic carcinomatosis and superimposed infection. The patient was palliated and passed away shortly thereafter. In the setting of UAPA, clinicians should have a high index of suspicion for the possibility of malignancy, and if proven, they should consider early resection following appropriate staging.